Manajemen Pendidikan Karakter dalam Mewujudkan Peserta Didik yang Berakhlakul Karimah - Nur Laeli (IBTIDA- Jurnal Kajian Pendidikan Dasar, 2022)
This research is motivated by the importance of character problems in students who are still inadequate. In this regard, this study aims to determine the management of character formation to realize the morals of students at MI Al-Muttaqin Binangun. This research is a qualitative type. Data collection through interviews, observation and documentation. The validity of the data using triangulation. Data analysis techniques include data reduction, data display, and drawing conclusions. This study resulted in five conclusions: (1) Character education planning is carried out through joint deliberations to determine the character and moral values ​​to be developed. And after the plan is completed, the next step is to instill values ​​and morality in students that aim to strengthen character education. These values ​​and morals are in line with the vision and mission of the madrasa. These values ​​and morals include: religious, sincere, hardworking, intelligent and caring. (2) Organizing character education, where the teacher becomes a role model for madrasah students is going well. These values ​​and morals are implemented in different ways depending on the style of each teacher. (3) Character education directives include activities that improve teacher-student relationships, provide opportunities for students to voice their opinions, and motivate students. (4) Control of character education is carried out by equipping students with the development of moral values ​​and literacy. These skills include: critical thinking, creative thinking, clear communication skills, listening skills, and good moral habits.